Implementación de una red inalámbrica de sensores de CO2 usando IoT como sistema de alerta ante una ventilación deficiente frente al Covid19 en aulas de clase (2023)
COVID-19 was identified in Wuhan, China in December 2019, and to date, has caused a devastating global pandemic [1]. The pathogen responsible for COVID-19 is mainly transmitted through aerosol droplets exhaled by infected individuals, which can remain suspended in the air of indoor spaces for up to 8 hours [2]. Therefore, monitoring the air quality in indoor spaces became relevant in order to try to reduce the contagion.